Benchmarking sugarcane irrigation management practices in Sub-Saharan Africa - Knox, Jerry W.; Banda, Mavuto Muhammad; Hess, Tim M. (Elsevier, 2026)
In many countries, irrigation is an essential component of sugarcane production to ensure consistently high yields. However, our evaluation of opportunities to improve irrigated cane production, based on data from selected estates across sub-Saharan Africa (SSA), characterised the region to have lower-than-expected yields ranging between 83.9 and 108.9 t/ha, excessive irrigation consumption and lower than potential water productivities – ranging between 5.0 and 7.8 kg/m3. Benchmarking irrigation performance across the sugarcane sector using a set of key performance indicators (KPIs) confirmed that there were a number of challenges linked to disparities in cane yields, water productivity and the environmental impacts of production. This confirmed that relying on continued expansion of cultivated areas simply to increase sugarcane production is an unsustainable long-term strategy. Performance gaps in relation to low yields, water productivity and inadequate irrigation management practices leading to excessive irrigation water use were identified as key signs of inadequate management practices. These aspects not only have significant implications on the sustainability of sugar business operations, but also on the environmental impacts of irrigated production. The study provides valuable insights on the interventions needed to improve irrigated sugarcane production across SSA with a focus on improving yields, and reducing irrigation and energy use at the business or estate level.
Keywords: Agricultural water management; Crop productivity; Irrigation systems; Performance gap; 30 Agricultural, Veterinary and Food Sciences; 2 Zero Hunger; Agronomy & Agriculture; 3002 Agriculture, land and farm management; 3004 Crop and pasture production; 4005 Civil engineering